(untitled) - Haag, Stephen (New York, N.Y., 2008)
BDT takes a business-first approach, improving students' perception of the value of IS within the business discipline. This perspective allows instructors to more easily demonstrate how technology and systems support business performance and growth.The adaptive chapter/plug-in organization enables the instructor to adjust content according to their business or technical preferences.
Keywords: Information technology,Management information systems,Information resources management,Industrial management,Quản trị công nghiệp,Quản trị công nghệ thông tin; Management,Technological innovations,Cải tiến kỹ thuật